The impact of heavy metal contamination on the morphology and physiology of small mammals - Greef, Dominique (My University, 2018)
Anthropogenic changes have resulted in a number of natural ecosystems being destroyed. One of the most destructive industries worldwide is mining, as it is responsible for habitat fragmentation, biodiversity loss, acid mine drainage and land use change, amongst others. While several authors have studied the interaction between heavy metals and plants, as well as larger animal species, only a few have investigated the effects of heavy metals on small mammals, particularly not in South Africa. The aim of this study was to investigate the impacts of heavy metal contamination on the morphology and physiology of small mammals in the Krugersdorp Game Reserve. Four sites within the reserve were sampled between September 2016 and January 2017 and heavy metals (Fe, U, As, Cd, Cu, Pb, Zn, Ni) known to occur in the reserve at high levels due to the nearby mine formed the basis for all heavy metal testing. Soil and vegetation samples were taken from each site and tested for heavy metal accumulation using ICP-OES. Rodents (in particular, Mastomys natalensis), were trapped using Sherman live traps and morphological measurements (body mass, body length, tail length and hind foot length) were taken for each trapped individual. Fifteen Mastomys individuals were euthanased and dissected to determine heavy metal concentrations in the spleens, livers and kidneys of these animals using ICP-OES. A number of heavy metals in the soil and vegetation exceeded recommended daily exposure levels for mammals and humans. No significant differences were found when adult morphological characteristics were compared across the sites in the reserve. Body length in Mastomys juveniles was significantly negatively correlated with all heavy metals measured in the soil and the vegetation in the reserve (U, As, Pb and Zn), except for Fe in the soil and Cu and Fe in the vegetation, which were positively correlated with the body length of juveniles. The same trend was found for body mass in the juveniles, with Pb in the vegetation also showing a positive correlation with body mass. The average morphological features of adult Mastomys individuals in this study were lower than the average body mass, body length, tail length and hind foot length of individuals not exposed to heavy metals contamination. No significant relationships were found between heavy metal concentrations in the soil and vegetation and the organs of the dissected individuals. Patterns indicating a link between high levels of heavy metals in the vegetation and high levels in the spleens of Mastomys individuals, as well as high levels of heavy metals in the soil and high levels in the kidneys and livers suggest that dietary intake and direct skin contact may be resulting in the bioaccumulation of heavy metals in the tissues of the rodents studied. High levels (above recommended maximum exposure limits) of heavy metals in the vegetation and soil, as well as physical impacts to internal organs of studied Mastomys individuals suggest that rodents in the reserve may be at risk of liver and kidney disease and necrosis. Although a limited data set was available for this study, based on the results obtained and comparison to other literature, it can be suggested that small mammals within the Krugersdorp Game Reserve are at risk of heavy metal toxicity and a number of associated diseases.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Master of Science Johannesburg, 2018
Keywords: Agriculture, Prehistoric; Ethnobotany; Palynology